PERTUMBUHAN IKAN KURO (Eleutheronema tetradactylum Shaw, 1804) DI MUARA SUNGAI KUMBE KABUPATEN MERAUKE - Anna K. Gebze; Irianis L. Latupeirissa (AGRICOLA, 2017)
Aimed of this research is to know the growth of Kuro (Eleutheronema tetradactylum Shaw, 1804) at Estuarine of Kumbe River, Merauke District. This research was conducted around three months start from June until August 2016. The methodology used in this research are survey and there are several parameters had measured such as measurement of body lenght, body weight and environmental factors of Kuro fish. Number of fish had found through the research is 357 and all of them are male with the body lenght around 234-225 mm and body weight 17 – 243 gr. Growth pattern of Kuro at estaurine of Kumbe River in Merauke District was allometric positive, which means gained of body weight more faster than the body lenght. Condition factors of Kuro are varied along the research and relatively small, it caused by fish were success collected mostly had small size and in growing stage of their life cycle.